Paying for the party : how college maintains inequality - Armstrong, Elizabeth A.; Hamilton, Laura T. (Laura Teresa) (Harvard University Press, 2013)
In an era of skyrocketing tuition and mounting concern over whether college is "worth it," the authors assess the state of American higher education. They provide a powerful exposé of unmet obligations and misplaced priorities, and explain in vivid detail why so many leave college with so little to show for it. Mapping different pathways available to students at a flagship Midwestern public university, the authors demonstrate that the most well-resourced and seductive route is a "party pathway" anchored in the Greek system, facilitated by the administration--and with serious disadvantages for the majority of students.